Sinuslift − Ein Überblick - Grimm, Jannik; Lutz, Rainer (Implantologie, 2021)
The sinus elevation procedure in its variants is a reliable and predictable method for increasing the local bone supply in the posterior maxilla. Bone substitute materials can be used as an equivalent alternative to autogenous bone grafts and score points due to their lack of donor site morbidity and resorption stability. When considering the different surgical procedures, the external sinus lift is still considered the technique with the most long-term data. Modifications such as the so-called graftless sinus lift show promising results. Short implants are increasingly coming into focus as another treatment alternative.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Autogenous bone; Bone graft; Bone substitute material; Posterior maxilla; Short implants; Sinus elevation